Modulation of calcium-binding proteins expression and cisplatin chemosensitivity by calcium chelation in human breast cancer MCF-7 cells. Issue 1 (January 2021) - Hodeify, Rawad; Siddiqui, Shoib Sarwar; Matar, Rachel; Vazhappilly, Cijo George; Merheb, Maxime; Al Zouabi, Hussain; Marton, John
Abstract: Cisplatin (CDDP) is currently one of the most effective FDA-approved treatments for breast cancer. Previous studies have shown that CDDP-induced cell death in human breast cancer (MCF-7) cells is associated with disruption of calcium homeostasis. However, whether the sensitivity of breast cancer cells to cisplatin is associated with dysregulation of the expression of calcium-binding proteins (CaBPs) remains unknown. In this study, we evaluated the effect of the intracellular calcium chelator (BAPTA-AM) on viability of MCF-7 cells in the presence of toxic and sub-toxic doses of cisplatin. Furthermore, this study assessed the expression of CaBPs, calmodulin, S100A8, and S100A14 in MCF-7 cells treated with cisplatin. Cell viability was determined using MTT-based in vitro toxicity assay. Intracellular calcium imaging was done using Fluo-4 AM, a cell-permeant fluorescent calcium indicator. Expression of CaBPs was tested using real-time quantitative PCR. Exposure of cells to increasing amounts of CDDP correlated with increasing fluorescence of the intracellular calcium indicator, Fluo-4 AM. Conversely, treating cells with cisplatin significantly decreased mRNA levels of calmodulin, S100A8, and S100A14. Treatment of the cells with calcium chelator, BAPTA-AM, significantly enhanced the cytotoxic effects of sub-toxic dose of cisplatin. Our results indicated a statistically significant negative correlation between calmodulin, S100A8, and S100A14 expression and sensitivity of breast cancer cells to a sub-toxic dose of cisplatin. We propose that modulating the activity of calcium-binding proteins, calmodulin, S100A8, and S100A14, could be used to increase cisplatin efficacy, lowering its treatment dosage while maintaining its chemotherapeutic value. Abstract : Cisplatin; Calcium-binding proteins; BAPTA-AM; Intracellular calcium.